Traditional medicinal plants in South Tyrol (northern Italy, southern Alps): biodiversity and use - Petelka, Joshua (J Ethnobiol Ethnomed, 2020)
BACKGROUND: Worldwide mountain regions are recognized as hotspots of ethnopharmacologically relevant species diversity. In South Tyrol (Southern Alps, Italy), and due to the region’s high plant diversity and isolated population, a unique traditional botanical knowledge of medicinal plants has flourished, which traces its history back to prehistoric times. However, changes in rural life and culture may threaten this unique biodiversity and cultural heritage. Our study aims to collect and analyze information on native plants used in traditional folk medicine, focusing on the preservation of botanical and cultural diversity. METHODS: Data were collected through a review of published material that documents traditionally used medicinal plants of South Tyrol in order to capture the total diversity of plants and their usage. We evaluated different parameters, comprising the ethnobotanicity index (EI), ethnophytonomic index (EPI), relative frequency of citation (RFC), red list status, and regional legislation with regard to the plant species. RESULTS: A total of 276 species, including 3 mushrooms and 3 lichens, were identified. These belonged to 72 families, most frequently to the Asteraceae, Rosaceae, and Lamiaceae. The most frequently cited species were Hypericum perforatum L., Urtica dioica L., and Plantago lanceolata L. According to 12 ICPC-2 disease categories, the most frequently treated human health symptoms were from the digestive and respiratory systems as well as the skin. A total of 27 species were listed as endangered, of which 16 are not protected and two are now already extinct. Among the 59 predominantly alpine species, 11 species are restricted to the high altitudes of the Alps and may be threatened by global warming. CONCLUSIONS: Our research revealed that the ethnobotanical richness of South Tyrol is among the highest in Italy and throughout the Alps. Nevertheless, it is evident that biodiversity and traditional knowledge have been heavily eroded. Furthermore, we point out particularly sensitive species that should be reconsidered for stronger protections in legal regulations.